Effect of Helicity and Rotation on the Free Decay of Turbulent Flows - Teitelbaum, Tomas (2009)
The self-similar decay of energy in a turbulent flow is studied in direct numerical simulations with and without rotation. Two initial conditions are considered: one nonhelical (mirror symmetric) and one with maximal helicity. While in the absence of rotation the energy in the helical and nonhelical cases decays with the same rate, in rotating flows the helicity content has a major impact on the decay rate. These differences are associated with differences in the energy and helicity cascades when rotation is present. The properties of the structures in the flow at late times are also discussed. © 2009 The American Physical Society.